What can general practice learn from primary care nurses' and healthcare assistants' experiences of the COVID-19 pandemic? A qualitative study. Issue 3 (15th March 2022) - Russell, Alice; de Wildt, Gilles; Grut, Minka; Greenfield, Sheila; Clarke, Joanne
Abstract : Objectives: UK general practice has radically altered in response to COVID-19. The general practice nursing team has been central to these changes. To help learn from COVID-19 and maintain a sustainable nursing workforce, general practice should reflect on their support needs and perceptions of organisational strategies. This study aimed to explore primary care nurses' and healthcare assistants' experiences and perceptions of general practice, and the changes made to it, during the pandemic. Design: Exploratory qualitative study using semistructured interviews. Interview data were analysed using Braun and Clarke's 'codebook' thematic analysis. Setting: General practices in the Midlands, South East and South West England. Interviews were conducted in February and March 2021, as England began to unlock from its third national lockdown. Participants: Practice nurses (n=12), healthcare assistants (n=7), advanced nurse practitioners (n=4) and nursing associates (n=1) recruited using convenience and snowball sampling. Results: Three themes were identified. Difficult changes describes dramatic changes made to general practice at the onset of the pandemic, creating confusion and anxiety. Dealing with change characterises how negative emotions were intensified by fear of infection, problematic government guidance, personal protective equipment (PPE) shortages and friction with doctors; but could be mitigated through effective practice communication, peer support and individual coping strategies. An opportunity for improvement highlights certain changes (eg, the increased use of telehealth) that participants believed could be adopted long term to improve efficiency. Conclusion: General practice should learn from the COVID-19 pandemic to nurture the clinical role and resilience of nurses and healthcare assistants in the postpandemic 'new normal'. Robust PPE provision could enable them to undertake their patient-facing duties safely and confidently. Judicious implementation of telehealth could help preserve the practical and caring nature of nursing. Improving channels of communication and interprofessional collaboration could help realise their potential within the primary care team.